The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1093/geront/45.suppl_1.74
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics Associated With Low Food and Fluid Intake in Long-Term Care Residents With Dementia

Abstract: This article describes the prevalence, assessment, and treatment of, as well as characteristics associated with, the food and fluid intake of 407 residents with dementia in 45 assisted living facilities and nursing homes. Overall, 54% of observed residents had low food intake, and 51% had low fluid intake. Staff monitoring of residents, having meals in a public dining area, and the presence of noninstitutional features were each associated with higher food and fluid intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
112
2
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(116 citation statements)
references
References 17 publications
1
112
2
1
Order By: Relevance
“…29e31 Of 4 studies judged low risk, 2 assessed serum osmolality, 20,22 1 used International Classification of Diseases, Ninth Revision (ICD-9) codes only, 25 and 1 measured all fluid intake over 24 hours using referenced methodology with good interrater reliability (r ¼ 0.98). 14 Of the 16 high-risk studies, 8 assessed fluid intake only, 11,15,17,19,23,24,26,33 4 assessed dehydration status, 12,13,21,28 and 4 used a combination of both fluid intake and dehydration assessment. 10,16,18,32 Fluid intake assessments were judged high risk if they were conducted for part of the day or method of ascertainment was not considered to be accurate, whereas dehydration assessments were judged high risk if they had not been validated against serum osmolality in an elderly population (urine specific gravity [USG], 16,21,32 urine color, 16 16,18 or Total Body Resistance [TBR]).…”
Section: Risk Of Bias Validity and Methodological Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…29e31 Of 4 studies judged low risk, 2 assessed serum osmolality, 20,22 1 used International Classification of Diseases, Ninth Revision (ICD-9) codes only, 25 and 1 measured all fluid intake over 24 hours using referenced methodology with good interrater reliability (r ¼ 0.98). 14 Of the 16 high-risk studies, 8 assessed fluid intake only, 11,15,17,19,23,24,26,33 4 assessed dehydration status, 12,13,21,28 and 4 used a combination of both fluid intake and dehydration assessment. 10,16,18,32 Fluid intake assessments were judged high risk if they were conducted for part of the day or method of ascertainment was not considered to be accurate, whereas dehydration assessments were judged high risk if they had not been validated against serum osmolality in an elderly population (urine specific gravity [USG], 16,21,32 urine color, 16 16,18 or Total Body Resistance [TBR]).…”
Section: Risk Of Bias Validity and Methodological Qualitymentioning
confidence: 99%
“…Reed et al 17 assessed the association of environmental factors with low fluid intake. The odds of a low fluid intake were lower for participants eating in the dining room compared with their bedrooms (OR 0.18; 95% CI 0.06e0.63).…”
Section: Physical and Social Setting For Drinkingmentioning
confidence: 99%
“…This result indicated that rats in all the ES groups had the same dehydration as the PS group. Fluid intake is associated with food intake, which can directly influence the body weight (Reed et al, 2004). During habituation and training periods, there was no difference in the changes of body weight among all the groups.…”
Section: The Changes In Fluid Intake and Body Weight Of The Ratsmentioning
confidence: 91%
“…This data set yielded some correlations between resident outcomes and the physical environment. For example, Reed, Zimmerman, Sloane, Williams, and Boustani (2005) reported that ''facility type was associated with intake, with residents of small RC/AL facilities less likely to have low food intake and residents of new-model RC/AL facilities less likely to have low fluid intake'' (p. 77).…”
Section: Physical Environmentmentioning
confidence: 99%